Comparative Study of the Physicochemical Properties of a Vegan Dressing-Type Mayonnaise and Traditional Commercial Mayonnaise - Cerro-Munoz, D; Matiacevich, S (CSIC Consejo Superior de Investigaciones Cientificas, 2021)
The food industry has developed a vegan dressing-type mayonnaise due to new consumer demands. The aim of this study was to compare three commercial mayonnaise types with a vegan dressing, measuring their physicochemical properties. Four dressing samples were analyzed: vegan, homemade recipe, creamy, and light. The following properties were measured: water activity, color, droplet size, rheological properties, structural analysis, and oxidative stability. A high color difference was observed between vegan and the other samples due to the presence of chickpea protein. The size and distribution of droplets of the vegan sample were greater than the others. The rheological properties indicated that all samples are non-Newtonian pseudoplastic fluids. The FT-IR results indicated that the highest peak for vegan corresponded to its content in mono-unsaturated fat. Therefore, it showed the lowest oxidative stability. In conclusion, the mayonaise formulations were affected by physicochemical properties such as the content and composition of the oil, thickener and protein contents, along with processing technology. © 2021 CSIC Consejo Superior de Investigaciones Cientificas. All rights reserved.